2012
DOI: 10.1155/2012/320198
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Somatostatin Analogues Therapy in Advanced Neuroendocrine Tumors: A Single Centre Experience

Abstract: The aim of this study was to assess the efficacy of PRRT in patients with advanced neuroendocrine tumors (NETs). Patients and Methods. From January 2007 to August 2011, we enrolled 65 patients (m/f 38/27; mean age 65 years, range 33–83) with advanced NETs having enhanced SSTR expression, treated with PRRT. The enhanced expression of SSTR was assessed using 68Ga-DOTATOC/DOTATATE PET/CT. Among all the enrolled patients, 6 of them were excluded from the present analysis since they voluntarily interrupted treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Toxicity was recorded throughout all the study and up to 6 months after completion. A comprehensive description of this clinical study and patients is reported in a companion paper [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Toxicity was recorded throughout all the study and up to 6 months after completion. A comprehensive description of this clinical study and patients is reported in a companion paper [13]. …”
Section: Methodsmentioning
confidence: 99%
“…90 Y, or a combination of the two. Data from nonrandomised clinical studies indicates that a response to treatment (complete or partial remission) can be achieved in approximately 8-46% of patients, and the mean progression-free survival after the treatment is 25 to 36 months [133][134][135][136][137][138][139][140][141]. These studies apply mostly to patients with well-differentiated neoplasms (G1 and G2), and these recommendations are for this group of patients.…”
Section: Poorly-differentiated Neoplasms (G3) -Neuroendocrine Carcinomasmentioning
confidence: 99%
“…In patients with a high somatostatin receptor expression, depending on the stage of the disease, PPRT may be considered as the first-line treatment [138,140].…”
Section: Place Of Isotope Treatment In the Therapy Of Advanced Neuroementioning
confidence: 99%
“…Positron emission tomography/computed tomography was performed on a hybrid scanner (Discovery STE; GE Healthcare, Chalfont St. Giles, UK in Centre A and Gemini GXL; Philips Medical Systems, Cleveland, OH or Biograph; Siemens Healthcare, Malvern, PA in Centre B). Images were acquired 60 ± 10 min after tracer injection (2 MBq/kg) as whole body (vertex‐feet) in both Centres according to protocols previously described …”
Section: Methodsmentioning
confidence: 99%